An Overview of Facial and Head and Neck Trauma at Patan Hospital - Shrestha, Namita; Dangol, Bhawana; Devkota, Ishwor Raj; Nepal, Ajit; Yadav, Deepak; Bhandary, Sangeeta (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To find out the prevalence of various types of head and neck trauma. Material and Methods: This retrospective study was done in the department of ENT and HNS, Patan Hospital, PAHS. Charts were retrospectively reviewed for total 61 inpatients with a diagnosis suggestive of head and neck trauma from August 2013 to January 2015. Data was collected for age, sex, address, type of admission (emergency/OPD), mechanism of injury, site of injury , imaging including X-rays/CT scan wherever applicable and results, surgical therapy, type of anesthesia, hospital admission duration, complications, and follow-up and analyzed. Result: Males were common than females (62.3% vs. 37.7%). Fall was the most common mode of injury (100%) in both pediatric and elderly population and in adults RTA (42.10%) was the most common mode. In the type of injury most common in pediatrics was oral cavity and oropharyngeal injury (47.60%), in adults facial soft tissue injury (STI) and facial fractures (42.10%) were equally common and in geriatrics it was (100%). Conclusion: Adult males were prone to head and neck trauma mostly sustaining soft tissue injury (STI) and fractures due to RTA and physical assult. Injury to oral cavity and oropharynx and STI due to fall is common in extreme of ages. Though the management out comes were good and no grave complications were reported in this study. Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015